miR-22-5p regulates the self-renewal of spermatogonial stem cells by targeting EZH2 - Lv Wenqiang; Yu Mei; Su Yilin (Open Medicine, 2022)
MiRNAs play an important role in spermatogonial stem cells (SSCs). The purpose of this study was to investigate the basic function of miR-22-5p in cryptorchidism. The results of RT-PCR, western blot, and immunohistochemistry showed that miR-22-5p was increased while EZH2 decreased in the testicular tissues of patients with cryptorchidism. Overexpression of miR-22-5p inhibited the proliferation of SSCs, increased cell apoptosis rate, and reduced expression of SSC marker proteins (GDNF and DAZL); however, knockout of miR-22-5p has the opposite effect. The Luciferase reporter gene assays demonstrated that EZH2 is a direct target of miR-22-5p. Moreover, EZH2 overexpression could reverse the effect of miR-22-5p mimic on SSCs’ proliferation, apoptosis, and expression of SSC marker proteins. Our results demonstrated that miR-22-5p regulates SSCs’ self-renewal by targeting EZH2, which indicated that miR-22-5p may serve as a biological marker for the treatment of infertility caused by cryptorchidism.